Casa della Cultura e Fondazione Corrente: confronto aperto e crescita (Materiali di Estetica. Terza serie, 2022)
The author recounts his experience of collaboration with the Casa della Cultura and later with Fondazione Corrente, combining the autobiographical aspect with a critical analysis. It was an opportunity for comparison between practical knowledge of art and theoretical visions expressed in the academic field. Starting from specific experiences in various fields of artistic expression, the Author reports the controversy on the centrality of beauty, in the different perceptions and conceptions of art, touching on issues that are generally rarely addressed
Keywords: Casa della Cultura; Fondazione Corrente; Aesthetics